Validity and Reliability of Learning Tools Based on Discovery Learning Model to Improve Creative Thinking Ability and Concept Understanding - Linda Lusiana Muslim; Ni Nyoman Sri Putu Verawati; Muh Makhrus (Lensa: Jurnal Kependidikan Fisika, 2021)
This study aimed to describe the validity and reliability of the based discovery learning models to improve creative thinking ability and students’ conceptual understanding of harmonic vibrations. The type of research used is research development (Research and Development) with the research design being developed is 4D Models. The subject of this research is the based discovery learning models to improve creative thinking ability and students’ conceptual understanding of harmonic vibrations. Retrieval of research data using validation sheets which were assessed by 3 expert validators consisting of 3 physics education lecturers. The research data is in the form of qualitative and quantitative data from the validator's assessment of the learning tools developed. The learning tools include syllabus, learning material, lesson plans, student worksheet, creative thinking ability test, and conceptual understanding test. This study conducted a validity test to determine the feasibility and validity level of the learning tools. The validity data obtained a value of 3.39 for the syllabus, 3.41 for the learning material, 3.27 for the lesson plan, 3.41 for the student worksheet, 3.37 for the creative thinking ability test and 3.33 for the conceptual understanding test. So that the average validity of learning tools is in the very valid category with a validity level of 3.36. Furthermore, the reliability test, the coefficient interval results obtained are 0.973 for the syllabus, 0.939 for the learning material, 0.976 for lesson plans, 0.982 for student worksheet, 0.958 for creative thinking ability test and 0.963 for conceptual understanding test. So that the average reliability coefficient interval is 0.965 with the reliable category. The conclusion is that the learning tools are valid and reliable for use in learning activities.